Rituximab versus tocilizumab in anti-TNF inadequate responder patients with rheumatoid arthritis (R4RA): A stratified, biopsy-driven, multi-centre, randomised, open label, controlled clinical trial - 16 week outcomes - Humby, F; Durez, P; Buch, MH; Lewis, M; Rizvi, H; Rivellese, F; Nerviani, A; Giorli, G; Mahto, A; Montecucco, C; Lauwerys, B; Ng, N; et al. (Elsevier, 2021)
Background: Although targeted biological treatments have transformed the outlook for patients with rheumatoid arthritis, 40% of patients show poor clinical response, which is mechanistically still unexplained. Because more than 50% of patients with rheumatoid arthritis have low or absent CD20 B cells—the target for rituximab—in the main disease tissue (joint synovium), we hypothesised that, in these patients, the IL-6 receptor inhibitor tocilizumab would be more effective. The aim of this trial was to compare the effect of tocilizumab with rituximab in patients with rheumatoid arthritis who had an inadequate response to anti-tumour necrosis factor (TNF) stratified for synovial B-cell status.